Does E-Service Quality in Banyuwangi’s Smartkampung Improve Public Satisfaction Directly and Through E-Trust? - Ahmad Fuad Hasan; Firda Hidayati; Alfi Haris Wanto; Sjamsiar Sjamsuddin; Andrean Nathaniel; Alfina Auliyaul Chusna (Jurnal Borneo Administrator, 2026)
Rapid developments in information technology require local governments to strengthen the quality of electronic public services; however, empirical studies examining how e-service quality shapes public satisfaction through e-trust in the context of local e-government applications remain limited. This study addresses this gap by analyzing the Smartkampung Banyuwangi super-application, one of the mostadvanced e-government implementations in Indonesia, to identify how e-service quality influences public satisfaction directly and indirectly through e-trust. Using an explanatory quantitative design, data were collected from 166 residents who used the Smartkampung application and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings demonstrate that e-service qualitysignificantly affects e-trust (β = 0.773; p < 0.001) and public satisfaction (β = 0.520; p < 0.001). E-trust also significantly influences satisfaction (β = 0.338; p < 0.001) and mediates the relationship between e-service quality and satisfaction (indirect effect β = 0.261; p < 0.001), with the model explaining 65.7% of the variance in satisfaction (R² = 0.657). The study contributes theoretically by extending e-servicequality and trust frameworks within village-level e-government services. In practice, the findings highlight the importance of improving system availability, efficiency, and data security to strengthen users’ trust and enhance satisfaction with digital public service delivery.